Effects of quality of opposition and match status on technical and tactical performances in elite volleyball - Marcelino, R.; Mesquita, I.; Sampaio, J. (Journal of Sports Sciences, 2011)
The aim of this study was to assess the effects of quality of opposition and match status on technical and tactical volleyball performances, as measured by block, attack, serve, and set actions related to the tasks, space, players, and efficacy of selected game actions. Twenty-five matches from the men's World Cup 2007 were notated and through cluster analysis were classified as "high" (HIGH), "intermediate" (INT) or "low" (LOW) quality. The difference between points scored and points allowed was used to define match status. Multinomial logistic regression identified an association of match status with: set direction (likelihood ratio test [LRT] = 15.5, P = 0.017) and block typology (LRT = 9.6, P = 0.047) in HIGH vs. HIGH matches; attack player (LRT = 17.4, P = 0.026) and block typology (LRT = 9.2, P = 0.010) in LOW vs. LOW matches; and serve type (LRT = 17.4, P = 0.002), block strategy (LRT = 53.7, P <0.001), and serve efficacy (LRT = 26.0, P = 0.001) in HIGH vs. LOW matches. Results suggest that volleyball teams took more risky decisions in unbalanced situations. They also carried less risk through technical and tactical decisions in balanced and moderate situations whether they had the advantage or not. Therefore, strategic behaviour was affected by the interaction of quality of opposition and match status, providing a better understanding of volleyball game performance and new insights for practice, competition, and research.